An analysis of annual environmental conditions and heat gains, and theoretical assessment of approaches to improve summer thermal comfort, of the Energy Research Centre at the University of Cape Town - Cunliffe, Guy Edward (Energy Research Centre, 2017)
The Energy Research Centre (ERC), a research centre located at the University of Cape Town (UCT), is considering retrofitting its offices with measures to improve its occupants' thermal comfort, particularly during Cape Town's summer months. While a simple solution would be to install an active cooling system, first consideration should be given to the deployment of preventative cooling measures and retrofits. By these means, the costs of an active cooling system would be reduced, as well as the building's relative increase in energy consumption and indirect greenhouse gas emissions. This dissertation examines internal thermal conditions of the ERC under current building conditions and predicts levels of thermal discomfort likely to be experienced by occupants, with emphasis on Cape Town's summer season. Heat gain components to the ERC are quantified, and a Base Case cooling scenario is determined; this characterises the peak cooling load and active annual cooling energy required to alleviate summer thermal discomfort, if no other interventions are implemented. Thereafter, the impacts of a selection of preventative cooling measures on the Base Case cooling scenario are assessed, and a theoretical payback period for each progressive measure is evaluated, relative to projected installation and operational costs of an active system designed to meet the Base Case. A model of the ERC offices is developed in DesignBuilder, which characterises thermal properties of the building envelope, thermal loads of lighting, electronic equipment and building occupants, and effects of prevailing weather patterns and solar radiation at the site of the building. Physical energy simulations of the model are run in EnergyPlus, which uses a series of algorithms based on the Heat Balance Method to quantify internal psychrometric conditions and heat gains in half-hourly iterations. An EnergyPlus Ideal Loads Air System component is input into the simulation to quantify the active cooling load required to maintain comfortable design conditions. The results indicate that 7 814.5 hours of thermal discomfort are experienced annually across the ERC (divided into eight thermal zones in the DesignBuilder model), with 37.6% of discomfort hours occurring between December and March, and 12.8% in February alone. Notably, a greater proportion of discomfort hours, 38.9%, were predicted for winter months (June through August). However winter thermal discomfort was not addressed in detail here, as the scope of the dissertation was limited to analysing ERC cooling only. Solar gains through external windows were found to be the largest single source of annual heat gain (20.65 MWhth), followed by heat gains due to lighting heat emissions (19.99 MWhth). Profiles during typical summer conditions showed significant heat gain also arises from conduction through the ceiling, due to existing but sporadic and thin layers of fibreglass ceiling insulation, with gaps that allow thermal bridging between the roof space and ERC thermal zones. The Base Case annual cooling requirements were determined to be 27.64 MWhth, while peak cooling load was found to be 66.87 kWth. Sensible cooling dominated total cooling loads in summer months. East and west facing thermal zones required the greatest cooling energy (normalised per floor area), having been shown to experience the greatest normalised solar and lighting heat gains. Inclusion of a 75 mm polyester fibre insulation layer above the ceiling boards would result in a 13.6% decrease in annual discomfort hours, relative to the current building condition, and reduced peak cooling load by 19% relative to the Base Case. Increasing thickness above 75 mm resulted in increased ceiling thermal resistance and further reduced annual discomfort hours. However, the marginal improvements in thermal comfort were found to decrease with increased insulation thickness. A 75 mm thickness of polyester fibre insulation was therefore selected as the first preventative measure to be considered for the ERC, and was included in all further assessment of additional preventative options. Lighting retrofits were also considered, by means of two progressive measures: Delamping – the removal of fluorescent luminaires from overly lit thermal zones – and Relamping – replacement of remaining fluorescents and light fixtures with more energy efficient technology (as well as the Delamping and Insulation measures). Delamping was found, from simulation analysis, to reduce lighting heat gains by 31%, relative to the Base Case and annual cooling requirements by 24%, with total projected costs after 10 years reduced by 15.6% relative to the Base Case. Relamping had a less pronounced impact on cooling requirements, but resulted in 15 % lower lighting energy use compared to Delamping only. The final measure considered was a Shading measure, whereby the replacement of the existing solar window film, currently fitted to each of the ERC's external windows, with internal adjustable shading. The Shading retrofit (in addition to all previous preventative measures) was found to cause a 35% reduction in annual cooling energy relative to the Base Case, as well as a 7% relative to the Relamping scenario. However, cost evaluation showed that costs of implementing the Shading retrofit significantly outweighed net incremental annual savings achieved under the measure, and was thus not recommended as a preventative option for the ERC. Alternative shading options, such as fixed external shading, may prove more cost effective in mitigating the ERC's solar heat gains, and should be considered in further research. From these results, it was concluded that a combination of insulation and lighting upgrades would provide the greatest benefit, in terms of thermal comfort, to the ERC, and would result in a more cost effective active cooling system, should one be proposed. The dissertation ended with recommendations for further work, including further analysis of ERC heating requirements in winter, and investigation into additional and alternative cooling methods, such as passive or solar cooling.